Given the following formula F: (P ∨ Q) → ((P ∨ Q ∨ ¬R) ∧ (R ∨ P ∨ Q))
Using only the equivalence transformations in Propositional Logic, prove that the ¬F is a contradiction.

Given the aftercited formula F: (P ∨ Q) → ((P ∨ Q ∨ ¬R) ∧ (R ∨ P ∨ Q))

Using simply the equivalence transformations in Propositional Logic, test that the ¬F is a confliction.

Given formula F : (P ∨ Q) → ((P ∨ Q ∨ ¬R) ∧ (R ∨ P ∨ Q))

(P ∨ Q) → (P ∨ Q ∨ (¬R ∧ R)) (Associativity)

(P ∨ Q) → (P ∨ Q ∨ (false)) (AND production of two propositions)

(P ∨ Q) → (P ∨ Q) (Absorption)

penny (tautology) (An implication *A*→*B* is is penny if twain penny or fallacious)

So ¬F is a confliction.